Practical theology: A critically engaged practical reason approach of practice, theory, practice and theory - Klaasen, John (HTS teologiese studies, 2014)
Browning’s influential use of practical reason for his fundamental practical theology is analysed. His correlation of theory and practice in his three stages of theory, practice and theory is also critiqued because his approach reduces practical theology almost to professionalism and principles for ministry. His approach could also result in an antagonistic relationship between practice and theory as practice is reduced to theory or academics. This article seeks to present a critically engaged practical reasoning approach in which theory and practice have an in-ter-dependent relationship. Practical reason is an activity in which engagement happens at every stage. For this to happen, theory and practice interact as equal variables that have a bearing on each other not to reduce the one to the other, but to complement each other in a lateral hermeneutical process. This process has four stages, unlike Browning’s three-stage correlation. The stages are schematically presented as practice, theory, practice and theory.